The Ecranization of Shichiri Nakayama's Novel Seiren no Zange - Stefanie Quin Manuhutu; Fithyani Anwar (Universitas Diponegoro, 2024)
This research aims to explain the ecranization process in the Seiren no Zange novel by Shichiri Nakayama into the Seiren no Zange drama series, as well as to analyze the impact of the ecranization process which includes aspects of reduction, addition and various changes to the story structure in plot, characters, and setting elements. The descriptive qualitative method used in this research is assisted by a structural approach. This research analysis uses the theory of ecranization. Ecranization is a form of transitioning a novel into an audiovisual display as a form of positive response or reaction to a literary work. The data collection regarding this research has been done through literature study and data sources from novels and drama series. In overall, based on the data that have been collected, this ecranization process resulted in 27 reductions, 77 additions and 25 varied changes. The produced data from this research is a form of ecranization of the novel into the Seiren no Zange drama series and the impact of the results of this ecranization. <a href=